Effects of Quadrifide Sterculia R. Br Extract on Potential of Membrane of Oreochromis Niloticus Egg Cell Resulting from Pb Contamination - Fetronela Rambu Bobu; Chomsin Sulistya Widodo; Johan Andoyo Effendi Noor (Natural B, Journal of Health and Environmental Sciences, 2016)
The effect of faloak (Sterculia quadrifida R.Br.) extract to the cell membrane potentials of tilapia (Oreochromis nilaticus) egg in contaminated water lead was studied. The cell membrane potential of tilapia egg was measured by a microelectrode connected to a Picoscope. The result showed that increasing of the Pb consentration caused decreasly of the membrane potential. Faloak extraction in contaminated water raised the membrane potential value. The concentration of faloak extract with the impact of raising the cell membrane potential of tilapia egg that have been contaminated by Pb is 0,8 mg. It seems that the antioxidant of faloak extract can reduce pollution rate.